2022
DOI: 10.1177/20552173221133262
|View full text |Cite
|
Sign up to set email alerts
|

Bright light therapy as a non-pharmacological treatment option for multiple sclerosis-related fatigue: A randomized sham-controlled trial

Abstract: Background Fatigue is a common symptom in people with multiple sclerosis (pwMS) that significantly impairs quality of life. Bright light therapy may be a cheap treatment option with little to no adverse events. Objectives To evaluate the effectiveness of bright light therapy as a treatment option for MS-related fatigue. Methods This was randomized sham-controlled trial including 26 pwMS with a Fatigue Severity Scale (FSS) Score ≥36. Participants were assigned to receive either bright white light therapy ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The comprehensive analysis of Table 3 enables a thorough discussion of the potential effects of various interventions on the clinical manifestations of these diseases. Red light therapy has shown promise in reducing fatigue severity in MS patients, with studies by [133] and [134] reporting improvements of 11.88% and 8.68%, respectively. Frequency-specific microcurrent therapy has demonstrated significant effects in reducing pain and disability in MS, with [135] reporting impressive improvements of 81.35% in pain reduction and 62.02% in reducing disability.…”
Section: Resultsmentioning
confidence: 99%
“…The comprehensive analysis of Table 3 enables a thorough discussion of the potential effects of various interventions on the clinical manifestations of these diseases. Red light therapy has shown promise in reducing fatigue severity in MS patients, with studies by [133] and [134] reporting improvements of 11.88% and 8.68%, respectively. Frequency-specific microcurrent therapy has demonstrated significant effects in reducing pain and disability in MS, with [135] reporting impressive improvements of 81.35% in pain reduction and 62.02% in reducing disability.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies revealed an improvement in fatigue scores after light therapy. However, neither of the studies revealed a significant treatment effect of bright white light when compared to sham therapy with dim red light 126,127 . Although both studies feature low sample sizes and did not investigate the effects of light therapy on circadian rhythmicity in MS, their results indicate that the effectiveness of light therapy might be limited in MS, potentially as a consequence of retino‐hypothalamic tract impairment.…”
Section: Circadian Disturbances In Msmentioning
confidence: 92%
“…Two studies investigated the effect of bright white light therapy for treating fatigue in pwMS. 126,127 Both studies revealed an improvement in fatigue scores after light therapy. However, neither of the studies revealed a significant treatment effect of bright white light when compared to sham therapy with dim red light.…”
Section: Retino-hypothalamic Tract Integritymentioning
confidence: 95%
See 2 more Smart Citations